Hippocampal neurons code individual episodic memories in humans - Kolibius, Luca D.; Roux, Frederic; Parish, George; Ter Wal, Marije; Van Der Plas, Mircea; Chelvarajah, Ramesh; Sawlani, Vijay; Rollings, David T.; Lang, Johannes; Gollwitzer, Stephanie; Walther, Katrin; Hopfengärtner, Rüdiger; et al. (Nature Human Behaviour, 2023)
The hippocampus is an essential hub for episodic memory processing. However, how human hippocampal single neurons code multi-element associations remains unknown. In particular, it is debated whether each hippocampal neuron represents an invariant element within an episode or whether single neurons bind together all the elements of a discrete episodic memory. Here we provide evidence for the latter hypothesis. Using single-neuron recordings from a total of 30 participants, we show that individual neurons, which we term episode-specific neurons, code discrete episodic memories using either a rate code or a temporal firing code. These neurons were observed exclusively in the hippocampus. Importantly, these episode-specific neurons do not reflect the coding of a particular element in the episode (that is, concept or time). Instead, they code for the conjunction of the different elements that make up the episode.
CRIS-Team Scopus Importer:2023-10-20

Spectral properties of bursts in therapeutic burst suppression predict successful treatment of refractory status epilepticus - Gollwitzer, Stephanie; Hopfengärtner, Rüdiger; Rampp, Stefan; Welte, Tamara; Madžar, Dominik; Lang, Johannes; Reindl, Caroline; Stritzelberger, Jenny; Köhn, Julia; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen B.; et al. (Epilepsy and Behavior, 2024)
Burst suppression (BS) on EEG induced by intravenous anesthesia (IVAT) is standard therapy for refractory status epilepticus (RSE). If BS has any independent therapeutic effect on RSE is disputed. We aimed to define EEG characteristics of BS predicting termination or recurrence of status after weaning. All RSE patients treated with IVAT while undergoing continuous EEG monitoring on the neurological intensive care unit between 2014 and 2019 were screened for inclusion. A one hour-period of visually preselected BS-EEG was analyzed. Bursts were segmented by a special thresholding technique and underwent power spectral analysis. Out of 48 enrolled patients, 25 (52.1 %) did not develop seizure recurrence (group Non SE) after weaning from IVAT; in 23 patients (47.9 %), SE reestablished (group SE). In group Non SE, bursts contained higher amounts of EEG delta power (91.59 % vs 80.53 %, p < 0.0001), while faster frequencies were more pronounced in bursts in group SE (theta: 11.38 % vs 5.41 %, p = 0.0008; alpha: 4.89 % vs 1.82 %, p < 0.0001; beta: 3.23 % vs 1.21 %, p = 0.0002). Spectral profiles of individual bursts closely resembled preceding seizure patterns in group SE but not in group Non SE. Accordingly, persistence of spectral composition of initial ictal patterns in bursts, suggests ongoing SE, merely interrupted but not altered by BS. Fast oscillations in bursts indicate a high risk of status recurrence after weaning from IVAT. EEG guided individualized sedation regimes might therefore be superior to standardized anesthesia protocols.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Intravenous anesthesia; Multimodal monitoring; Quantitative EEG